Enhancing Community Health Development through Women’s Empowerment and Social Roles in Posyandu Management: A Case Study in Buring, Malang City - Nuriya Kartika Sari; Harsuko Riniwati; Fitri Candra Wardana; Ahmad Mulyasir (Jurnal Pemberdayaan Masyarakat, 2026)
This study aims to analyze the influence of women's empowerment and women's social roles on community health development through the implementation of Posyandu (Pos Pelayanan Terpadu) in Buring Sub-district, Kedungkandang District, Malang City. The research method is quantitative, with a Structural Equation Modeling (SEM) approach using Partial Least Squares (PLS). The research sample consisted of 176 respondents, including pregnant women, mothers of toddlers, toddler companions, and elderly (senior citizens). The results of the study indicate that women's empowerment has a positive and significant effect on the implementation of Posyandu and on community health development. In addition, women's social roles positively contribute to community health development by strengthening the implementation of Posyandu, a community-based primary health care institution. Posyandu serves as a mediating variable, strengthening the influence of women's empowerment and social roles on the community's health status. This finding emphasizes the importance of enhancing women's leadership capacity, active participation in health programs, and their role as agents of social change.